Are admission laboratory values in isolation meaningful for predicting surgical outcome in patients with perforated peptic ulcers? - Mulder, Wikus W.; Arko-Cobbah, Emmanuel; Joubert, Gina (Elsevier, 2023)
Background The study aimed to calculate the predictive value of admission laboratory values in patients with perforated peptic ulcers. Methods A retrospective, cohort analytical, observational study was performed, including patients with surgically confirmed perforated peptic ulcers over a 5-year period. Demographic data and admission laboratory values were collected from hospital electronic databases. Outcomes measured were in-hospital mortality, intensive care unit (ICU) admission and length of stay. The significance of categorical variables was calculated by chi-square and Fisher's exact test. Logistic regression analysis was performed to determine univariately statistically significant variables. Results In total, 188 patients met the inclusion criteria. The median age was 46 (range 15–87) years with a male predominance of 71.3 % (n = 134). The median length of hospital stay was 7 (range 1–94) days and 31.4 % (n = 59) of patients were admitted to the ICU. Post-operative in-hospital mortality was 25.0 % (n = 47). Predicting the categorical outcome of in-hospital mortality, abnormal haemoglobin, platelet count, urea, creatinine and potassium levels were all found to be statistically significant in the univariate analysis. Age (odds ratio [OR] 1.03), haemoglobin (OR 4.36) and creatinine (OR 7.76) levels were significant in the multivariate analysis. Conclusions Mortality rate among patients with perforated peptic ulcer disease is still substantial. Admission laboratory values showed statistical significance as outcome indicators and were valuable to assist in predicting the prognosis. An abnormally high serum creatinine level was the strongest single predictor of both mortality and ICU admission. Key message Initial laboratory findings of patients admitted for perforated peptic ulcer showed that an abnormally high serum creatinine level was the strongest single predictor of both mortality and ICU admission.
Keywords: Peptic ulcer; Perforation; Emergency surgery; Mortality; Laboratory values